2007
DOI: 10.3892/ijmm.20.4.527
|View full text |Cite
|
Sign up to set email alerts
|

Effect of scopoletin on lipoprotein lipase activity in 3T3-L1 adipocytes

Abstract: Abstract. Hypertriglyceridemia is an independent risk factor of cardiovascular diseases. It is caused by the imbalance between hepatic triglyceride production and peripheral removal. Lipoprotein lipase (LPL) plays a central role in the removal of plasma triglyceride. During the screening of possible anti-dyslipidemic drugs, we observed that scopoletin (6-methoxy-7-hydroxycoumarin) significantly increased LPL activity in adipocytes. Scopoletin increased LPL activity in culture medium of 3T3-L1 adipocytes in dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…In addition, the relative opacity of the lenses incubated for 3 days of treatment of compound 1 was dosedependently reduced to 79.24 ± 7.90% (10 µM) and 72.87 ± 12.40% (25 µM), respectively. Scopoletin (1, 6-methoxy-7-hydroxy coumarin) has been isolated from many plant sources and has been shown various pharmacological effects such as anti-inflammatory, antioxidant, acetylcholinesterase inhibitory, antithyroid, antihyperglycemic, and lipoprogein lipase activities (Muschietti et al, 2001;Shaw et al, 2003;Rollinger et al, 2004;Sunanda and Anand, 2006;Yang et al, 2007). To the best of our knowledge, AGEs formation inhibitory activity of 1 and RLAR inhibitory activity of 4 were have not been reported previously.…”
Section: Resultsmentioning
confidence: 85%
“…In addition, the relative opacity of the lenses incubated for 3 days of treatment of compound 1 was dosedependently reduced to 79.24 ± 7.90% (10 µM) and 72.87 ± 12.40% (25 µM), respectively. Scopoletin (1, 6-methoxy-7-hydroxy coumarin) has been isolated from many plant sources and has been shown various pharmacological effects such as anti-inflammatory, antioxidant, acetylcholinesterase inhibitory, antithyroid, antihyperglycemic, and lipoprogein lipase activities (Muschietti et al, 2001;Shaw et al, 2003;Rollinger et al, 2004;Sunanda and Anand, 2006;Yang et al, 2007). To the best of our knowledge, AGEs formation inhibitory activity of 1 and RLAR inhibitory activity of 4 were have not been reported previously.…”
Section: Resultsmentioning
confidence: 85%
“…Phytosterols reduce the absorption of cholesterol in the gut and thereby lower blood cholesterol levels [ 36 ]. Scopoletin is a stimulator of lipoprotein lipase activity and protects against cardiovascular diseases [ 37 ]. Lignans improve immune responses [ 38 ].…”
Section: Phytochemical Composition Of Urtica Spmentioning
confidence: 99%
“…Recent data have shown that TNFα infusion can induce systemic lipolysis in human subjects ( 40 ) . Treatment with TNFα in vitro increases glycerol release from rodent and human adipocytes, probably by inhibiting lipoprotein lipase activity ( 41 ) and down regulating the expression of perilipin, which then enables hormone-sensitive lipase to access the surface of lipid droplets ( 42 ) . TNFα-induced adipocyte lipolysis is the outcome of activation of the TNFα receptor 1-dependent pathway ( 43 , 44 ) , which involves the stimulation of extracellular signal-regulated kinase 1 and 2, mitogen-activated protein kinase, c-Jun N-terminal kinase and protein kinase A ( 45 , 46 ) .…”
Section: Potential Mediators Of Adipose Atrophymentioning
confidence: 99%